Pembelajaran Matematika dengan Pendekatan Open-Ended bagi Siswa SD - Iflia, Witri; Yusaini, Yusaini; Rahayu, Nina; Sari, Rita (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2021)
For students to be able to think critically and cognitively, it needs to be stimulated with the right approach so that they can meet the goals that they want to achieve in learning. The purpose of this research is to describe the application of an open-ended approach to math lessons and describe students' learning activities. This type of research is by class action research, the instruments used are observation sheets and test learning results. The results showed that an open-ended approach could be applied to high-graders with attention to student characteristics. Students' learning activities are also getting better and more active during the learning. While the learning outcomes are also improving. So this open-ended approach can be applied by teachers, especially in math lessons.